2000
DOI: 10.1038/sj.ejhg.5200426
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure of the gene for the human P1 protein (MCM3) and its exclusion as a candidate for autosomal recessive polycystic kidney disease

Abstract: The locus PKHD1 (polycystic kidney and hepatic disease 1) has been linked to all typical forms of the autosomal recessive polycystic kidney disease (ARPKD) and maps to chromosome 6p21.1-p12. We previously defined its genetic interval by the flanking markers D6S1714 and D6S1024. In our current work, we have fine-mapped the gene for the human P1 protein (MCM3), thought to be involved in the DNA replication process, to this critical region. We have also established its genomic structure. Mutation analyses using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…1A). The genes KIAA0057 (Onuchic et al 1999), FLJ10466 (Onuchic et al, in press), MCM3 (Hofmann et al 2000), Interleukin-17 (Rouvier et al 1993), and ML-1 (Kawaguchi et al 2001) have been described elsewhere. Each of these genes either has been excluded as a candidate for PKHD1 or, on the basis of its known function, has been deemed to be an unlikely candidate.…”
Section: Transcription Map Of the Minimal Intervalmentioning
confidence: 99%
“…1A). The genes KIAA0057 (Onuchic et al 1999), FLJ10466 (Onuchic et al, in press), MCM3 (Hofmann et al 2000), Interleukin-17 (Rouvier et al 1993), and ML-1 (Kawaguchi et al 2001) have been described elsewhere. Each of these genes either has been excluded as a candidate for PKHD1 or, on the basis of its known function, has been deemed to be an unlikely candidate.…”
Section: Transcription Map Of the Minimal Intervalmentioning
confidence: 99%
“…Two independent groups recently unraveled the PKHD1 gene (9,10). Ward et al identified the human gene by homology to the mutation in the PCK rat model for polycystic kidney disease (11,12), and our group succeeded by positional cloning (13)(14)(15)(16). On genomic DNA, the gene spreads over an expanse of at least 470 kb.…”
mentioning
confidence: 99%
“…2). KIAA0057 and MCM3 have been excluded as PKHD1 candidates [Onuchic et al, 1999; Hofmann et al, 2000], and IL‐17 and ML‐1 have expression patterns and functions unlikely to be involved with ARPKD pathogenesis. The hCT1642763 gene [Venter et al, 2001] is currently under evaluation, along with several other partial transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The MCM3‐A/B marker, a single nucleotide polymorphism, has been described previously [Hofmann et al, 2000].…”
Section: Methodsmentioning
confidence: 99%